1986
DOI: 10.1177/0148607186010003258
|View full text |Cite
|
Sign up to set email alerts
|

Elemental Diet Administered Nasogastrically without Starter Regimens to Patients with Inflammatory Bowel Disease

Abstract: The present study questions the concept of routinely using 'starter regimens' at the outset of enteral feeding with chemically defined elemental diets. A hypertonic elemental diet with an osmolality of 630 mOsm/kg was administered by 24-hr nasogastric infusion to 12 patients with exacerbations of inflammatory bowel disease and to two patients with short bowel syndrome. Starter regimens were not used. Upper gastrointestinal symptoms of nausea, abdominal bloating, and colicky pain occurred transiently in only fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

1988
1988
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 11 publications
0
11
0
Order By: Relevance
“…55 ETF related diarrhoea occurs in up to 30% of enterally fed patients on medical and surgical wards and more than 60% of patients on intensive care units. [70][71][72][73][74] It can create serious problems from nutrient, fluid, and electrolyte losses, and from infected pressure sores and general patient distress. 55 Parenteral nutrition may be required if elimination of all other causes of gastrointestinal upset and/or administration of simple symptomatic treatments fails to resolve the problem.…”
Section: Reflux and Inhalation Problemsmentioning
confidence: 99%
“…55 ETF related diarrhoea occurs in up to 30% of enterally fed patients on medical and surgical wards and more than 60% of patients on intensive care units. [70][71][72][73][74] It can create serious problems from nutrient, fluid, and electrolyte losses, and from infected pressure sores and general patient distress. 55 Parenteral nutrition may be required if elimination of all other causes of gastrointestinal upset and/or administration of simple symptomatic treatments fails to resolve the problem.…”
Section: Reflux and Inhalation Problemsmentioning
confidence: 99%
“…Controlled clinical trials have convincingly demonstrated that the use of starter regimens only results in limiting the nutritional intake in the first few days of feeding, thereby prolonging the length of negative nitrogen balance. Except for critically ill patients and patients with short bowel syndrome, dilutional starter regimes should not be used routinely [62,63].…”
Section: Starter Regimesmentioning
confidence: 99%
“…However such ''buildup'' regimens often serve only to provide inadequate nitrogen and energy. 64 Bolus feeding may cause more problems with bloating and diarrhea than continuous feeding, and therefore continuous infusion of enteral feeding is usually the recommended delivery method. 65 However, there is current renewed interest in the place of the older technique of bolus feeding, in the context of delayed gastric emptying.…”
Section: Delivery Of Feedmentioning
confidence: 99%